2010
DOI: 10.4067/s0718-95162010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Degradation and Bioremediation of Chlorinated Herbicides and Biphenyls

Abstract: Chlorinated herbicides (e.g. s-triazines) and polychlorobiphenyls (PCBs) are persistent organic pollutants (POPs) that are widely distributed in the environment. s-Triazine herbicides are used in agriculture and forestry in diverse regions of the world. PCBs were produced worldwide for industrial applications, and an important amount of these compounds have been released into the environment. PCBs and s-triazines are toxic compounds that could act as endocrine disrupters and cause cancer. Therefore, environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 76 publications
2
26
0
Order By: Relevance
“…The HPLC results confirmed that these results were reliable as the screening for the compound following extraction of the same aliquot product of the experiment did not show the presence of the compound. The degradation of PCBs by Pseudomonas strains from Notwane Sewage Treatment Plant has not been reported before and thus these results suggest that strains from Gaborone wastewater have the ability to degrade recalcitrant compounds as reported from other studies in different areas [7,25,27].…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The HPLC results confirmed that these results were reliable as the screening for the compound following extraction of the same aliquot product of the experiment did not show the presence of the compound. The degradation of PCBs by Pseudomonas strains from Notwane Sewage Treatment Plant has not been reported before and thus these results suggest that strains from Gaborone wastewater have the ability to degrade recalcitrant compounds as reported from other studies in different areas [7,25,27].…”
Section: Resultssupporting
confidence: 66%
“…The shifts are an indication of the presence of initial ring oxidation metabolites and ring fission metabolites [25,27] PCBs first get degraded into chlorobenzoates [27] that have been found to have λ max ranging from 244-270nm in the C-band when dissolved in water [28], a range that was observed in the results obtained after 24 hours of incubation of treated wastewater with bacterial isolate MD2 used in this study and PCBs aroclor 1260 (Figure 1) which proves that the bacteria was able to breakdown the compound. The product chlorobenzoate is biodegraded into benzoate and eventually pyruvate and acetyladehyde which are essential in the tricarboxylic cycle (TCA) [25,27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic algae and microorganisms mutated with bioluminescence genes could be using in biomonitoring of organic and inorganic pollution 133,134 . Expression of the catabolic genes of PCB-degrading microorganisms is a key factor for biodegradation of PCBs 135 . Transgenic plants expressing the bacterial xenobiotic degradation genes combine the advantages of both the systems.…”
Section: By Genetic Engineeringmentioning
confidence: 99%
“…Bioremediation is an attractive technology for removal of POPs from the environment (Atlas and Philp, 2005;Morgante et al, 2010;Seeger et al, 2010;Ponce et al, 2011). Degradation of alkanes by Alcanivorax borkhumensis SK2, Pseudomonas putida GPo1 and Acinetobacter baylyi ADP1 has been characterized (Ratajczak et al 1998;van Beilen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%